Numerical analysis of hydrodynamic force of front- and rear-stator pump-jet propulsion systems behind a submarine under oblique sailing. (15th December 2022) - Peng, Huanghua; Guo, Jiamin; Sun, Yu; Wang, Geng; Qu, Lixin
Abstract: The underwater vehicles' pump-jet propulsion capacity may affect during oblique sailing. In this study, the hydrodynamic performance of pump-jet propulsors installed on the stern of a Suboff submarine model was investigated under the oblique sailing condition. It can provide a theoretical basis of the hydrodynamic design of pump-jets under complex conditions. The computational domain of the pump-jet propulsor was divided with a trim mesh, and a calculation model based on the shear stress transport k - ω model was established. Then the unsteady hydrodynamic performance of the pump-jet propulsor was calculated using a sliding mesh technique. Once grid independence and the reliability of the calculation method had been verified, the flow field distributions were compared for various inflow angles ( β ). The flow field complexity of pump-jet propulsors during oblique sailing could be increased from the stator arrangement. As the inflow angle increases, the front stator rectification efficiency gradually becomes greater than the rear stator (wake recovery) efficiency. At β  = 30°, the rear stator no longer has excellent oblique wake recovery. However, the front stator limits the effect of the oblique wake on the rotor. Thus, front-stator pump-jet propulsors are more effective in adverse environments such as at β  = 30°. Highlights: The full-size Suboff submarine is used to provide nonuniform wake for pump-jet propulsors. The flow and pressure field distributions of front- and rear-stator pump-jets are simulated under oblique sailing. The front-stator pump-jet propulsor is easy to adapt to complex sea conditions, such as oblique sailing.